MOTOR SPAREPART SALES APPLICATION NEW SEI KAMAH RUDI SPARE PARTS SHOP - Suparmadi Suparmadi; Parini Parini; Mhd. Ihsan (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Technology plays an important role in trading business management. The sales application is a system that performs data processing and financial transactions that are equipped with integrated management such as sales transaction processes such as cash registers and inventory calculations or stock items. the role of this goods sales application can simplify the operational form they need and be able to increase their work effectiveness. The main objective of software procurement is to replace manual operations with technology, which is able to make the business survive in the midst of business competition and be able to develop according to expectations. Rudi Sparepart Store is a motorcycle spare parts sales store located in Sei Kamah Baru, Sei Dadap District which is engaged in sales, especially motorcycle spare parts and all motorcycle accessories. By implementing a sales application at the Rudi Spare Parts Store, it can help the shop admin process sales transactions for motorbike spare parts and reports can be generated quickly. Keywords: application; sales ; spare parts  Abstrak: Teknologi memegang peranan penting dalam manajemen bisnis perdagangan. Aplikasi penjualan merupakan suatu sistem yang melakukan pengolahan data serta transaksi keuangan yang dilengkapi dengan manajemen terintegrasi seperti proses transaksi penjualan seperti mesin kasir dan perhitungan inventory atau stok barang. peran aplikasi penjualan barang ini dapat mempermudah bentuk operasional yang mereka butuhkan dan mampu meningkatkan efektivitas kerja mereka. Tujuan utama pengadaan perangkat lunak adalah untuk menggantikan operasi manual dengan teknologi, yang mampu membuat bisnis bertahan di tengah persaingan bisnis dan mampu berkembang sesuai harapan. Rudi Sparepart Store merupakan toko penjualan sparepart sepeda motor yang berlokasi di Sei Kamah Baru , Kecamatan Sei Dadap yang bergerak di bidang penjualan khususnya spare part sepeda motor dan segala aksesoris sepeda motor. Dengan mengimplementasikan aplikasi penjualan di Toko Sparepart Rudi dapat membantu admin toko dalam memproses transaksi penjualan spare part motor dan laporan dapat dihasilkan dengan cepat. Kata kunci: aplikasi; penjualan ; suku cadang